The Effectiveness of Using Rubber Ball Throwing Game to Teach Vocabulary - Mukminatus Zuhriyah; Rizqi Aziza (Universitas Nurul Jadid, 2022)
The research aimed to find out student vocabulary mastery before and after being taugh by using Rubber Ball Throwing Game. It used pre eksperiment design. This research was conducted in SMPN 5 Jombang The sample in this study were students of class VIII-F of SMPN 5 Jombang for the academic year 2021-2022. The researcher analyzed the data using t-test through SPSS V.25. After collecting the data, the researcher got the pre-test and post-test scores with the mean pre-test was 79.23. and the mean value of the post test is 89.42. Then, the researcher analyzed the data using the t test, the results of Sig. (2-tailed) which is lower than 0.05. It can be stated that Ha is accepted. Based totally at the results of data analysis, several conclusions were obtained, namely the vocabulary of students before being taught using a rubber ball throwing game which looked low to be better after being taught using a rubber ball throwing game and there was a significant difference between students' vocabulary mastery before and after being taught using a rubber ball throwing game. Thus, it can be concluded that the use of rubber ball throwing game is effective for teaching vocabulary to class VIII-F students of SMPN 5 Jombang.